2019
DOI: 10.1002/art.40739
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Anti–Citrullinated Protein Antibody–Producing B Cell Clones From Rheumatoid Arthritis Patients

Abstract: Objective Anti–citrullinated protein antibodies (ACPAs) are a hallmark of rheumatoid arthritis (RA). Aside from autoantibody production, the function of autoantigen‐specific B cells remains poorly understood in the context of this disease. This study set out to elucidate autoantigen‐specific B cell functions through the isolation and immortalization of unique citrullinated protein/peptide (CP)–reactive B cell clones from RA patients. Methods B cell clones from either the blood or synovial fluid of cyclic citru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…It is intriguing to hypothesize that ACPA subsets, based on reactivity fingerprints and consensus motifs, may be associated with different pathogenic properties. Polyclonal ACPAs have been observed to modulate both osteoclast and fibroblast functionality, have proinflammatory properties, and mediate pain behavior (22,24–26,48–50). Our previous studies demonstrated that the ACPA clone 1325:04C03 (with the Gly–Cit motif) have osteoclastogenic properties and have no effect on fibroblasts (22,23,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing to hypothesize that ACPA subsets, based on reactivity fingerprints and consensus motifs, may be associated with different pathogenic properties. Polyclonal ACPAs have been observed to modulate both osteoclast and fibroblast functionality, have proinflammatory properties, and mediate pain behavior (22,24–26,48–50). Our previous studies demonstrated that the ACPA clone 1325:04C03 (with the Gly–Cit motif) have osteoclastogenic properties and have no effect on fibroblasts (22,23,51).…”
Section: Discussionmentioning
confidence: 99%
“…The included ACPA mAb have been described previously and have been verified to have citrulline reactivity down to a concentration of at least 100 ng/ml (22,24–26). All recombinant ACPA mAb were expressed as human IgG1 in Expi 293 cells (Life Technologies), and the mAb were purified with protein G resin (GE Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…The transduced cells were sorted into wells with flow cytometry and cultured in the presence of CD40L and IL‐21. Supernatants were screened for citrullinated peptide reactivity by ELISA and the ACPA clone 1003:10A01 was identified . RA blood memory derived ACPA positive clone obtained by EBV immortalization : The ACPA positive blood memory derived clone BVCA1 was isolated from RA PBMC using methods previously described . Briefly, CD22 + cells were enriched using MACS microbeads (Miltenyi) and subsequently sorted for IgG + cells.…”
Section: Methodsmentioning
confidence: 99%
“…In combination with cell sorting, it also allows subsequent analysis, such as transcriptomic profiling by single cell‐based (“next generation”) sequencing techniques. Furthermore, it is possible to analyze antigen‐specific B cell receptor (BCR) repertoires, to obtain full‐length BCR sequences for mAb generation, and to perform functional studies of isolated single B cells or B cell populations, which includes the generation of immortalized, antigen‐specific B cell clones . This wealth of possibilities permits unprecedented insights into human B cell biology; it requires, however, particular care and adherence to relevant and tedious control steps to ensure that the antigen‐specific B cell populations identified by FCM, which are frequently very rare, indeed represent the antigen‐specific B cell population of interest.…”
Section: Introductionmentioning
confidence: 99%